THE USE OF POLITENESS STRATEGIES IN CINDERELLA MOVIE SCRIPT (2015) - Arinda Dea Mutiasari; Didit Kurniadi (Jurnal CULTURE (Culture, Language, and Literature Review), 2019)
Politeness is an important thing in communication because we need to understand someone’s feeling. The problem of this research is about politeness strategies on Cinderella (2015) movie consisting of bald-on record strategy, positive politeness strategy, negative politeness strategy, and off-record indirect strategy. The objectives of the study are to determine politeness strategies which are used by the character in Cinderella (2015) movie script to determine the factors that influences the choice of politeness strategies. The research methodhology is qualitative with observation and instropection. The result shows that the movie contains four politeness strategies in the conversation between the characters. The use of politeness strategies to emphasize each conversation depends on who they are talking to Keywords: Politeness, Cinderella, Movie, Strategies